ANTARA PAJAK DAN HARGA TIKET : TANTANGAN FISKAL MASKAPAI INDONESIA DI TENGAH GEMPURAN MASKAPAI REGIONAL ASEAN - Harahap, Subur; Wibowo, Edi Wahyu (JURNAL LENTERA BISNIS, 2026)
Indonesia’s aviation industry plays a crucial role in national connectivity but faces significant challenges from regional competitors offering lower ticket prices. Domestic airlines bear heavier fiscal burdens, including aviation fuel taxes, VAT on tickets, and non-tax state revenues, which increase operational costs and reduce competitiveness. Using a comparative qualitative approach, this paper examines Indonesia’s fiscal policies against those of neighboring countries such as Singapore and Malaysia. Findings show that higher taxation weakens domestic airlines’ market position, while regional carriers benefit from lighter fiscal regimes and subsidies. Policy recommendations include reducing aviation fuel taxes, providing VAT incentives, and subsidizing airport infrastructure to strengthen the competitiveness of Indonesian airlines.